ISRN.MATHEMATICAL.ANALYSIS ISRN Mathematical Analysis 2090-4665 Hindawi Publishing Corporation 145606 10.1155/2013/145606 145606 Research Article On the Positive Operator Solutions to an Operator Equation Yang Kai-Fan 1 Deng Fang-An 1 Du Hong-Ke 2 Lindstrom M. Lurie K. A. 1 School of Mathematics and Computer Science Shaanxi University of Technology, Shaanxi 723001 China snut.edu.cn 2 College of Mathematics and Information Science Shaanxi Normal University, Xi'an 710062 China snnu.edu.cn 2013 26 6 2013 2013 03 05 2013 09 06 2013 2013 Copyright © 2013 Kai-Fan Yang et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

The necessary conditions and the sufficient condition for the existence of positive operator solutions to the operator equation Xs+A*X-tA=Q are established. An iterative method for obtaining the positive operator solutions is proposed.

1. Introduction

Let () be the set of all bounded linear operators on the Hilbert space . In this paper, we consider the nonlinear operator equation (1)Xs+A*X-tA=Q, where A,Q(), Q>0, and X is an unknown operator in (). Both s and t are positive integers.

This type of equation often arises from many areas such as dynamic programming , control theory [2, 3], stochastic filtering and statistics, and so forth [4, 5]. In the recent years, for matrices, (1) has been considered by many authors (see ), and different iterative methods for computing the positive definite solutions to (1) are proposed in finite-dimensional space. The case s=t=1 has been extensively studied by several authors. In this paper, we extend the study of the operator equation (1) from a finite-dimensional space to an infinite-dimensional Hilbert space. We derive some necessary conditions for the existence of positive solutions to the operator equation (1). Moreover, conditions under which the operator equation (1) has positive operator solutions are obtained. Based on Banach’s fixed-point principle, we obtain the positive operator solution to the operator equation (1). First, we introduce some notations and terminologies, which are useful later. For A(), if (Ax,x)0 for all x, then A is said to be a positive operator and is denoted by A0. If A is a positive operator and invertible, then denote A>0. For A and B in (), AB means that A-B is a positive operator. For A(), A*, ω(A), σ(A), and r(A) denote the adjoint, the radius of numerical range, the spectrum, and the spectral radius of A, respectively.

For positive operators in (), the following facts are well known.

If PQ>0, then P-1Q-1.

Denote λmax(P)=max{λ:λσ(P),P>0},λmin(P)=min{λ:λσ(P),P>0}. Then λmin(P)IPλmax(P)I.

If the sequence {Xn}n=1+ of positive operator is monotonically increasing and has upper bound, that is, XkXk+1C1, or is monotonically decreasing and has lower bound, that is, C2Xk+1Xk, then this sequence is convergent to a positive limit operator, where C1,C2() are given operators.

2. Main Results and Proofs

In order to prove our main result, we begin with some lemmas as follows.

Lemma 1.

Let A,B(). If AB0, then AB.

Lemma 2.

Let A and B be self-adjoint operators in (). If AB, then, for every T(), one has T*ATT*BT.

In this section, we give our main results and proofs.

Theorem 3.

If the operator equation (1) has a positive operator solution X, then (1)AQ-1A*tXQs and (2)r(A)(bt/(s+t))t/2s(bs/(s+t))1/2, where b=Q.

Proof.

(1) If the operator equation (1) has a positive operator solution X, then 0A*X-tAQ. Hence, we obtain XsQ; that is, XQs. From A*X-tAQ, it follows that (2)Q-1/2A*X-t/2X-t/2AQ-1/2I,X-t/2AQ-1/2Q-1/2A*X-t/2I,AQ-1A*Xt. That is, XAQ-1A*t.

(2) From (1), we have (3)Xt+s+Xt/2A*X-tAXt/2=Xt/2QXt/2λmax(Q)Xt. Then (4)r(A)2=r2(Xt/2AX-t/2)Xt/2AX-t/22λmax(Q)Xt-Xt+s. According to the spectral decomposition of X, we have (5)λmax(Q)Xt-Xt+s=σ(X)(λmax(Q)λt-λt+s)dEλ. Denote λmax(Q)=Q=b. Then (6)λmax(Q)Xt-Xt+smaxλ(0,bs]|bλt-λt+s|=(bts+t)t/s(bss+t). Therefore, r(A)(bt/(s+t))t/2s(bs/(s+t))1/2.

Theorem 4.

If A is invertible and A*X-tAQ-(AQ-1A*)s/t for all X[AQ-1A*t,Qs], then (1) has a positive operator solution.

Proof.

Let Φ(X)=(Q-A*X-tA)1/s; then Φ is continuous for X[AQ-1A*t,Qs]; Φ(X)Qs; and Φ(X)[Q-(Q-(AQ-1A*)s/t)]1/s=(AQ-1A*)1/t. So Φ maps [AQ-1A*t,Qs] into itself. Furthermore, Φ is continuous on [AQ-1A*t,Qs] because X>0; hence, Φ has a fixed point in [AQ-1A*t,Qs]; that is, there exists X0 such that (Q-A*X-tA)1/s=X; this implies that (1) has a positive operator solution.

Theorem 5.

If the operator equation (1) has a positive operator solution X, then λmin(T*T)(t/(t+s))t/s(s/(t+s)) and Xα~Qs when λmin(T*T)1, where T=Q-t/2sAQ-1/2 and α~ is a solution to the equation αt/s(1-α)=λmin(T*T) in [t/(t+s),1].

Proof.

We consider the sequence (7)α0=1,αk+1=1-λmin((Q-t/2sAQ-1/2)*Q-t/2sAQ-1/2)αkt/s,k=0,1,2,.

Let X be a positive solution to (1). Then Xs=Q-A*X-tAQ=α0Q; that is, Xα0Qs. Assuming that XαkQs, then (8)Xs=Q-A*X-tAQ-A*Q-t/sAαkt/s=Q1/2[I-Q-1/2A*Q-t/2sQ-t/2sAQ-1/2αkt/s]Q1/2Q1/2×[1-λmin((Q-t/2sAQ-1/2)*Q-t/2sAQ-1/2)  αkt/s]×Q1/2=αk+1Q. Hence, XαnQs for all n=0,1,2,. It is straightforward to check that the sequence {αn} is monotonically decreasing; also, {αn} is bounded below; hence, {αn} is convergent. Denote T=Q-t/2sAQ-1/2 and let limnαn=α~; then α~=1-λmin(T*T)/α~t/s; that is, α~ is a solution to the equation αt/s(1-α)=λmin(T*T). Let f(x)=xt/s(1-x). Then (9)maxx[0,1]f(x)=f(tt+s)=(tt+s)t/s(st+s). Thus, it follows that λmin(T*T)(t/(t+s))t/s(s/(t+s)).

Since (10)λmin(T*T)(tt+s)t/s(st+s). Then the equation αt(1-α)=λmin(T*T) may have two solutions; one of these solutions is in the interval [t/(t+s),1].

In order to prove that the limit α~ of the sequence {αn} is in [t/(t+s),1], we assume that αit/(t+s) (obviously α0=1>t/(t+s)); then (11)αi+1=1-λmin(T*T)αit/s1-λmin(T*T)(t+st)t/s1-(tt+s)t/s(st+s)(t+st)t/s=tt+s. Therefore, αit/(t+s) for each i=1,2,. Since XαnQs, then Xα~Qs and α~[t/(t+s),1]. The proof is completed.

Consider the following iterative sequence: (12)X0s=γQ,Xk+1s=Q-A*Xk-tA,k=0,1,,γ>0.

We will prove the following theorem.

Theorem 6.

If the operator equation (1) has a positive operator solution X, then it has a maximal one XL. Moreover, the sequence {Xi} in (12) for γ[α~,1] is monotonically decreasing and converges to XL, where α~ is defined in Theorem 5.

Proof.

Consider the iterative sequence (12) with γ[α~,1]. According to Theorem 4, we have Xsα~QγQ=X0s for any positive operator solution X to (1).

Suppose that XisXs. Then (13)Xi+1s=Q-A*Xi-tAQ-A*X-tA=Xs.

Hence, XiX hold for each i. According to the definition of α~ and the monotonicity of the function f(x)=xt/s(1-x) on [t/(t+s),1], we have (14)γt/s(1-γ)Iα~t/s(1-α~)I=λmin(T*T)IT*T for all γ[α~,1], where T=Q-t/2sAQ-1/2. We compute (15)X1s=Q-A*(γQ)-t/sA=Q1/2[I-Q-1/2A*(γQ)-t/sAQ-1/2]Q1/2=Q1/2(I-γ-t/sT*T)Q1/2. Using inequality (14) and equality (15), we obtain X1sγQ=X0s.

Assuming that XisXi-1s, then (16)Xi+1s=Q-A*Xi-tAQ-A*Xi-1-tA=Xis. Therefore, Xi+1sXis for all i=0,1,; that is, the sequence {Xns} is monotonically decreasing. Hence, {Xns} converges to the positive operator solution XL to (1). Since XLsXs for any positive operator solution X, it follows that XL is the maximal solution.

Theorem 7.

Let λmin(T*T)<λmax(T*T)(t/(t+s))t/s(s/(t+s)), and β1,β2 are solutions to the equation βt/s(1-β)=λmax(T*T) in [0,t/(t+s)] and [t/(t+s),1], respectively. Then there are the following conclusions.

If γ[β1,β2], then the sequence {Xn} in (12) is monotonically increasing and converges to a positive operator solution Xγ[γQs,α~Qs] to (1).

If γ[α~,1], then the sequence {Xn} in (12) is monotonically decreasing and converges to the maximal positive operator solution XL[β2Qs,α~Qs] to (1).

If γ(β2,α~) and (t/s)A2(β2λmin(Q))(s+t)/s, then the sequence {Xn} in (12) converges to the unique solution XL[β2Qs,α~Qs], where α~ and T are defined in Theorem 5.

Proof.

Consider the function f(x)=xt/s(1-x),x[0,1]. It is monotonically increasing on [0,t/(t+s)] and monotonically decreasing on [t/(t+s),1], and (17)maxx[0,1]f(x)=f(tt+s)=(tt+s)t/s(st+s). Since λmax(T*T)(t/(t+s))t/s(s/(t+s)), then, for each γ1,γ2 such that 0<β1γ1β2<α~γ21, the inequalities (18)γ2t/s(1-γ2)Iλmin(T*T)T*Tλmax(T*T)γ1t/s(1-γ1)I are satisfied.

(i) Let γ[β1,β2]. We will prove that the operator sequence {Xn} in (12) is monotonically increasing and is bounded above.

According to the fourth inequality in (18), we compute (19)X1s=Q-A*(γQ)-t/sA=Q1/2(I-γ-t/sQ-1/2A*Q-t/sAQ-1/2)Q1/2=Q1/2(I-γ-t/sT*T)Q1/2γQ=X0s.

Assuming that XisXi-1s, then (20)Xi+1s=Q-A*Xi-tAQ-A*Xi-1-tA=Xis. Therefore, Xi+1sXis for all i=0,1,; that is, the sequence {Xns} is monotonically increasing. Obviously X0s=γQβ2Qα~Q. We suppose that Xisα~Q; from the first inequality in (18), we obtain (21)Xi+1s=Q-A*Xi-tAQ-A*(α~Q)-t/sAα~Q.

Hence, {Xns} converges to a positive operator solution Xγs to (1). Since Xi[γQs,α~Qs] for all i=0,1,, we have Xγ[γQs,α~Qs].

(ii) Let γ[α~,1]. From the proving procession of Theorem 6, the sequence (12) is monotonically decreasing. Since X0=γQsβ2Qs and supposing that Xisβ2Q, it follows that (22)Xi+1s=Q-A*Xi-tAQ-A*(β2Q)-t/sA=Q1/2(I-β2-t/sQ-1/2A*Q-t/sAQ-1/2)Q1/2Q1/2(I-β2-t/sλmax(T*T)I)Q1/2=β2Q. By induction principle, Xisβ2Q hold for each i=0,1,2,. Hence, {Xns} is convergent. From Theorem 6, {Xns} converges to XLs such that XL[β2Qs,γQs].

(iii) Considering the sequence {Xns} in (12) for γ(β2,α~), that is, X0s(β2Q,α~Q) and supposing that Xis(β2Q,α~Q), then, for Xi+1s, (23)Xi+1s=Q-A*Xi-tA<Q1/2(I-β2-t/sQ-1/2A*Q-t/sAQ-1/2)Q1/2α~Q,Xi+1s=Q-A*Xi-tA>Q1/2(I-α~-t/sQ-1/2A*Q-t/sAQ-1/2)Q1/2β2Q. Hence, Xis(β2Q,γQ), for all i=0,1,2,. Now, we considering Xi+1s-Xis, (24)Xi+1s-Xis=(Q-A*Xi-tA)-(Q-A*Xi-1-tA)1s1(β2λmin(Q)s)s-1×tA2(β2λmin(Q)s)t+1Xi-Xi-1=tsA21(β2λmin(Q)s)t+s×Xi-Xi-1, and (t/s)A2(β2λmin(Q))(s+t)/s, it follows that {Xn} in (12) is a Cauchy sequence in the Banach space [β2Qs,α~Qs]. Hence, it has a limit Xγ in [β2Qs,α~Qs], and Xγ is a unique solution to (1) in [β2Qs,α~Qs]. According to Theorem 6, it is the maximal solution, that is, Xγ=XL. The proof is completed.

Acknowledgments

This paper is supported by the NSF of China Grant no. 11171197 and by the Natural Science Foundation of Shaanxi Educational Committee Grant no. 12JK0884.

Pusz W. Woronowicz S. L. Functional calculus for sesquilinear forms and the purification map Reports on Mathematical Physics 1975 8 2 159 170 MR0420302 10.1016/0034-4877(75)90061-0 ZBL0327.46032 Engwerda J. C. On the existence of a positive definite solution of the matrix equation X+A*X-αA=I Linear Algebra and its Applications 1993 194 91 108 10.1016/0024-3795(93)90115-5 MR1243822 ZBL0798.15013 Green W. L. Kamen E. W. Stabilizability of linear systems over a commutative normed algebra with applications to spatially-distributed and parameter-dependent systems SIAM Journal on Control and Optimization 1985 23 1 1 18 10.1137/0323001 MR774025 ZBL0564.93054 Bucy R. S. A priori bounds for the Riccati equation 111 Proceedings of the 6th Berkeley Symposium on Mathematical Statistics and Probability 1972 Berkeley, Calif, USA University of California Press 645 656 Probability Theory MR0410150 Hasanov V. I. Solutions and perturbation theory of nonlinear matrix equations [Ph.D. thesis] 2003 Sofia, Bulgaria Ran A. C. M. Reurings M. C. B. On the nonlinear matrix equation X+A*F(X)A=Q: solutions and perturbation theory Linear Algebra and its Applications 2002 346 15 26 10.1016/S0024-3795(01)00508-0 MR1897819 Hasanov V. I. Positive definite solutions of the matrix equations X±A*X-qA=Q Linear Algebra and its Applications 2005 404 166 182 10.1016/j.laa.2005.02.024 MR2149658 ZBL1078.15012 Ran A. C. M. Reurings M. C. B. The symmetric linear matrix equation Electronic Journal of Linear Algebra 2002 9 93 107 MR1896373 ZBL1002.15015 Yang K. F. Du H. K. Studies on the positive operator solutions to the operator equations X+A*X-tA=Q Acta Mathematica Scientia A 2009 26 2 359 364 MR2518960 ZBL1210.47034 Yang Y. Duan F. Zhao X. On solutions for the matrix equation Xs+A*X-tA=Q Proceedings of the 7th International Conference on Matrix Theory and Its Applications in China 2006 21 24 Peng Z.-y. El-Sayed S. M. Zhang X.-l. Iterative methods for the extremal positive definite solution of the matrix equation X+A*X-αA=Q Journal of Computational and Applied Mathematics 2007 200 2 520 527 10.1016/j.cam.2006.01.033 MR2289231 ZBL1118.65029 Yueting Y. The iterative method for solving nonlinear matrix equation Xs+A*X-tA=Q Applied Mathematics and Computation 2007 188 1 46 53 10.1016/j.amc.2006.09.085 MR2327091 ZBL1131.65039 Hasanov V. I. El-Sayed S. M. On the positive definite solutions of nonlinear matrix equation X+A*X-δA=Q Linear Algebra and its Applications 2006 412 2-3 154 160 10.1016/j.laa.2005.06.026 MR2182958 ZBL1083.15018